Involvement of NRN1 gene in schizophrenia-spectrum and bipolar disorders and its impact on age at onset and cognitive functioning. (17th February 2016) - Fatjó-Vilas, Mar; Prats, Claudia; Pomarol-Clotet, Edith; Lázaro, Luisa; Moreno, Carmen; González-Ortega, Itxaso; Lera-Miguel, Sara; Miret, Salvador; Muñoz, Ma José; Ibáñez, Ignacio; Campanera, Sílvia; Giralt-López, Maria; et al.
Abstract: Objectives Neuritin 1 gene ( NRN1 ) is involved in neurodevelopment processes and synaptic plasticity and its expression is regulated by brain-derived neurotrophic factor (BDNF). We aimed to investigate the association of NRN1 with schizophrenia-spectrum disorders (SSD) and bipolar disorders (BPD), to explore its role in age at onset and cognitive functioning, and to test the epistasis between NRN1 and BDNF .Methods The study was developed in a sample of 954 SSD/BPD patients and 668 healthy subjects. Genotyping analyses included 11 SNPs in NRN1 and one functional SNP in BDNF .Results The frequency of the haplotype C-C (rs645649–rs582262) was significantly increased in patients compared to controls ( P = 0.0043), while the haplotype T-C-C-T-C-A (rs3763180–rs10484320–rs4960155–rs9379002–rs9405890–rs1475157) was more frequent in controls ( P = 3.1 × 10 −5 ). The variability at NRN1 was nominally related to changes in age at onset and to differences in intelligence quotient, in SSD patients. Epistasis between NRN1 and BDNF was significantly associated with the risk for SSD/BPD ( P = 0.005).Conclusions Results suggest that: (i) NRN1 variability is a shared risk factor for both SSD and BPD, (ii) NRN1 may have a selective impact on age at onset and intelligence in SSD, and (iii) the role of NRN1 seems to be not independent of BDNF.